Clostridium Difficile Infection in the Nephrology Ward - Sylwia Dudzicz; Marcin Adamczak; Andrzej Więcek (Karger Publishers, 2017)
Clostridium difficile is currently the most frequently identified pathogen causing antibiotic-associated diarrhea and the main cause of nosocomial diarrhea. In recent years, increases incidence of infection, severe infection, recurrent infection and mortality from Clostridium difficile infection (CDI) have been observed. This may be a consequence of excessive antibiotic use and spread of the hypervirulent epidemic BI/NAP1/027 strain of Clostridium difficile. The main risk factors for CDI are: antibiotic therapy, previous hospitalizations and number of comorbid conditions. Prevention of CDI mainly is focused in two directions: reducing the exposure of patients to the disease pathogen by intensifying hygiene measures, and reducing the impact of risk factors. A meta-analyses of clinical studies (observational, cohort and case control) showed significantly higher risk of CDI and CDI recurrence in patients with chronic kidney disease and increased mortality risk in chronic kidney disease patients with CDI comparing those without CDI. Increased risk of CDI in patients with chronic kidney disease can be caused by: frequent antibiotic therapy associated with numerous infections resulting in intestinal microflora dysfunction, frequent hospitalizations, older age of the patients and an impaired immune system. Among preventative measures against CDI, the use of probiotics were also studied. In patients hospitalized in nephrology ward highly significant reduction of the CDI incidence was observed after the introduction of Lactobacillus plantarum 299v as CDI prophylaxis. Therefore, the use of Lactobacillus plantarum 299v seems to be a promising method of CDI prevention in chronic kidney disease patients hospitalized in nephrology ward.